Negarawan Muslim Modern: Studi Tokoh Mohammad Natsir (1908-1993) dalam Pergaulan Multikultural - Naufal Al-Zahra (PT. Student Rihlah Indonesia, 2026)
This article aims to reveal the character, exemplary character, and legacy of M. Natsir (1908-1993), a modern Muslim figure of the 20th century for his role in building multicultural relations. This study of this figure was conducted to show evidence of the harmony of a Muslim's morals with the spirit of maintaining national unity amidst the diversity of Indonesian society. This research uses a historical research method consisting of 1) topic selection, 2) source collection (heuristic), 3) verification, 4) interpretation, and 5) writing history with the system cards research technique. To obtain a comprehensive picture of this study, a biographical and interpretative research approach was used through the concept of multicultural education proposed by Bhiku C. Parekh. The research results show that Natsir was an inclusive figure who proactively raised awareness of the importance of fostering the integrity of the Indonesian nation which is blessed with ethnic, cultural, and religious diversity. Some of Natsir's exemplary values ​​that have been revealed in this article include that he was a Muslim who was not allergic to differences, always embraced diversity, and demonstrated inclusive and principled behavior. These values ​​strengthen Natsir's exemplary role for the Indonesian nation, especially Muslims today, to achieve the vision of Indonesia Emas 2045.